Survey research in Africa : its applications and limits - O'Barr, William M.; Spain, David H.; Tessler, Mark A. (Evanston : Northwestern University Press, 1973)
The book is a series of discussions on preliminary social change in Africa dealing specifically with problems encountered during survey.
Bibliography: p. 303-334.
sju 23/01/2019
Loans
Keywords: Social surveys; Social sciences